Boosting 21st Century Skills through Moroccan ELT Textbooks - Hassan Ait Bouzid (Yayasan Visi Intan Permata, 2016)
Research shows that the changing realities of the 21st century necessitate a fundamental shift in language education towards promoting 21st Century Skills. This paper investigates the extent to which three Moroccan ELT textbooks currently used in teaching second year Baccalaureate students in public high school provide activities that help learners build skills that match the needs of the 21st century. It also explores the types of activities that are used to promote these skills and eventually suggests some ways in which these skills could be promoted effectively in future textbooks. It draws the attention of teachers, educational policy makers, school inspectors and textbook designers to the importance of incorporating activities that facilitate the acquisition of a set of skills that meet the demands of the 21st century. The study adopts a concurrent triangulation design and used content analysis as a mixed method that combines quantitative and qualitative techniques. Quantitative findings show that textbooks tend to provide very little activities that enable learners to develop their ICT skills. Also, they do not encourage learners to think creatively and develop career and life-skills. Qualitative findings indicate that textbooks tend to present these skills in a traditional way that does not cater for the 21st century context. This paper concludes with suggesting activities that will help future textbooks present 21st Century Skills in ways that will facilitate the transfer of these skills to Moroccan English language learners.